Standards Management Of Covid-19 Prevention According To world Health Organization (WHO) - Samsudin Samsudin; Dinda Ayu (Jurnal PKM Manajemen Bisnis, 2022)
Covid 19 is a health disaster that has hit the whole world, so that response actions are needed from all parties, to be able to take care of themselves, one of which is by socializing healthy movements through proper hand washing, based on WHO standards. This service activity is carried out in the midst of community groups who are members of the Leaf Salam Farmer Women's Group - RW 018 Pondok Benda, South Tangerang. This PKM activity is a form of real contribution from academics in dealing with the COVID-19 pandemic situation, by providing training on hand washing with WHO standards. The method of activity is carried out through the method of explanation, practice, and discussion. During the activity, all the material was conveyed well, and can be followed by all activity participants. Thus, this activity can add insight and knowledge of the community, especially in the Leaf Salam Farmer Women's Group (KWT) - RW 018 Pondok Benda about preventing covid 19 through proper hand washing.